Measuring socioeconomic inequalities in postnatal health checks for newborns in Ethiopia: a decomposition analysis - Hagos, Asebe; Tiruneh, Misganaw Guadie; Abera, Kaleab Mesfin; Tsega, Yawkal; Endawkie, Abel; Negash, Wubshet Debebe; Workie, Amare Mesfin; Yohannes, Lamrot; Getnet, Mihret; Worku, Nigusu; Belay, Adina Yeshambel; Asmare, Lakew; et al. (Frontiers in Public Health, 2024)
Background Addressing health inequity is a top priority for achieving sustainable development goals. The existing evidences in Ethiopia have shown that there are substantial inequalities in the use of health services among various socioeconomic strata. Therefore, the present study aimed to measure socioeconomic inequalities and the contributing factors in postnatal health checks for newborns in Ethiopia. Methods We used a secondary data from the recent 2019 Ethiopia Mini Demographic and Health Survey dataset. The study includes a weighted sample of 2,105 women who gave birth in the 2 years preceding to the survey. The study participants were selected using two stage cluster sampling techniques. The socioeconomic inequality in postnatal health checks for newborns was measured using the Erreygers Normalized Concentration Index (ECI) and illustrated by the concentration curve. A decomposition analysis was done to identify factors contributing to the socioeconomic related inequality in postnatal health checks for newborns in Ethiopia. Results The concentration curve of postnatal health checks for newborns lay below the line of equality, and the Erreygers normalized concentration index was 0.133, with a standard error = 0.0333, and a p value <0.001; indicating that the postnatal health check for newborns was disproportionately concentrated among newborns with higher socioeconomic status. The decomposition analysis reported that antenatal care (ANC) visit (59.22%), household wealth index (34.43%), and educational level of the mother (8.58%) were the major contributors to the pro-rich socioeconomic inequalities in postnatal health checks for newborns. Conclusion The finding revealed that there is a pro-rich inequality in postnatal health checks for newborns in Ethiopia. To reduce the observed socioeconomic health inequality, the government needs to improve ANC visits, implement strategies to access health service for economically disadvantaged groups, and increase educational attainment among women.